1998
DOI: 10.1007/s11663-998-0099-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inclusion re-entrainment from the steel-slag interface

Abstract: The mechanism of inclusion elimination from continuous steel casting is investigated at the steelslag interface. Inclusion impact at the interface is considered under the concept of energy balance, with buoyancy forces, fluid dynamic forces, interfacial adhesion, and rebound forces determining whether the particle will pass through the interface or be retained by it. The effects of the inclusion, slag, and steel properties, as well as the effect of inclusion impact velocity, are considered at the interface. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 5 publications
3
44
0
Order By: Relevance
“…It indicates that the bigger inclusions are more easily to be removed than smaller ones. Similar to the current findings, Bouris et al 23) reported that the larger inclusion can be more easily removed than smaller one.…”
Section: Chemical Compositions Of the Inclusionssupporting
confidence: 92%
“…It indicates that the bigger inclusions are more easily to be removed than smaller ones. Similar to the current findings, Bouris et al 23) reported that the larger inclusion can be more easily removed than smaller one.…”
Section: Chemical Compositions Of the Inclusionssupporting
confidence: 92%
“…Phenomena such as these are difficult to measure or to accurately quantify with a physical model, so are worthy of mathematical modeling. For example, a model of inclusion entrainment from the slag layer was developed by Bouris et al 132) …”
Section: Pressure Balance Methodsmentioning
confidence: 99%
“…Considering water modeling conditions, the walls are set as reflection boundary in this work for comparison of separation ratios of inclusion in SFT and a tundish with TI. Although most reports assume that the free surface is a trap boundary, there is a possibility of re-entrainment 18) to be considered. Given that the fluid is incompressible (i.e.…”
Section: Methodsmentioning
confidence: 99%